PERLINDUNGAN ANAK DALAM DILEMA PENEGAKAN HUKUM : ANTARA HAK ANAK DAN PENETAPAN DISPENSASI NIKAH DI PENGADILAN AGAMA KOTA TEGAL NO. 30/PDT.P/2020/PA.TG - Nurfatah Zulmi Arif Rahman; Khoirul Asfiyak; Dwi Ari Kurniawati (Jurnal Hikmatina, 2020)
AbstractMarriage is the law of God that is written in His book the Qur'an which has an important meaning where the cause of marriage raises broad laws, family law and the general public. Among the legal consequences are the issue of the minimum age of marriage to protect the rights of children who are married at an early age as stipulated in article 7 paragraph (1) and (2) with Law number 16 of 2019 concerning Marriage and Law number 35 years 2014. This research was conducted at the Tegal City Religious Court with a descriptive qualitative method that was presented objectively in accordance with facts on the ground. Namely by the interview of the judge concerned and written data from the judge's decision and analyzing the relevance of the judge in deciding the determination of marriage dispensations by considering the Child Protection Act number 35 of 2014. Keywords: Child Protection, Law Enforcement, Marriage Dispensation and Children's Rights